Micropropagação e conservação in vitro de acessos de patchouli Pogostemon cablin (Blanco) Benth.] - Santos, Aline Vieira (2010)
Patchouli is an aromatic species of Asian origin that has been cultivated in various parts of the world for the extraction of essential oil of its leaves. The essential oil is used by the perfume, cosmetic and food industries. Patchouli is an economically important species need to have its genetic material preserved. In this context, the aim of this study was to develop protocols for micropropagation and in vitro conservation of three accessions of patchouli. For the experiments of micropropagation MS medium supplemented with different concentrations of kinetin and IAA or NAA were tested. For the acclimatization assays different mixtures of coconut coir and vermiculite supplemented with NPK fertilizer and limestone were tested. For callus induction, different doses of 2,4-D were combined with BAP and kinetin. For the in vitro conservation assays different growth temperatures, osmotic regulators and/or inhibitors of growth were tested. The different accessions showed shoot regeneration via direct organogenesis. Accession POG002 can be propagated using 0.5 mg.L-1 kinetin and 0.1 mg.L-1 NAA, accession POG014 using 2.0 mg L-1 kinetin and 0.1 mg.L-1 NAA, and accession POG021 using 1.0 mg.L-1 kinetin and 0.5 mg.L-1 IAA. The acclimatization of accessions POG002, POG014 and POG021 can be performed with the substrate coconut coir + NPK (3-12-6) fertilizer (12 g.L-1) + limestone (1 g.L-1). The larger sizes of calluses were obtained using: 0.022 mg.L-1 2,4-D and 0.113 mg.L-1 BAP, 0.022 mg.L-1 2,4-D and 0.225 mg.L-1 BAP and 0.110 mg.L-1 2,4-D and 0.113 mg.L-1 BAP for accession POG014; 0.022 mg.L-1 2,4-D and 0.113 mg.L -1 BAP, 0.022 mg.L-1 2,4-D and 0.225 mg.L-1 BAP for POG021; and 0.022 mg.L-1 2,4-D and 0.225 mg.L-1 BAP for POG002. The conservation of accession POG002 can be realized using 0.5 mg.L-1 abscisic acid for three months at 18°C; accession POG014 can be conservated for three months using 0.5 mg.L-1 of abscisic acid at 18°C; and POG021 can be maintained for six months using sucrose 10 g.L-1 and sorbitol 5 g.L-1 at 25°C.